The Landau Strategy: How Working Women Win Top Jobs. - Landau, Suzanne and Geoffrey Bailey (New York Clarkson N. Potter, 1980)
Draws on the techniques of modern marketing to help working women overcome the psychological, social, and economic pressures that hinder them from advancing
Keywords: Economics